2020
DOI: 10.1038/s41598-020-69672-x
|View full text |Cite
|
Sign up to set email alerts
|

A footprint of plant eco-geographic adaptation on the composition of the barley rhizosphere bacterial microbiota

Abstract: The microbiota thriving in the rhizosphere, the thin layer of soil surrounding plant roots, plays a critical role in plant’s adaptation to the environment. Domestication and breeding selection have progressively differentiated the microbiota of modern crops from the ones of their wild ancestors. However, the impact of eco-geographical constraints faced by domesticated plants and crop wild relatives on recruitment and maintenance of the rhizosphere microbiota remains to be fully elucidated. Here we performed a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 80 publications
2
40
0
Order By: Relevance
“…The effect of geographical location on the microbiome has been discovered in other plants such as barley (Terrazas et al, 2020) and Gymnadenia conopsea (Lin et al, 2020), and significant variation has been reported. Each location in the present study harbored unique bacteria that could be used as a geographical indicator.…”
Section: Microbial Genera Specific To Geographical Locationmentioning
confidence: 99%
“…The effect of geographical location on the microbiome has been discovered in other plants such as barley (Terrazas et al, 2020) and Gymnadenia conopsea (Lin et al, 2020), and significant variation has been reported. Each location in the present study harbored unique bacteria that could be used as a geographical indicator.…”
Section: Microbial Genera Specific To Geographical Locationmentioning
confidence: 99%
“…For seed germination, seeds were placed on petri dishes containing semi-solid agar media at 0.5 % concentration. After a week, seedlings displaying a comparable development were individually transferred into 12-cm pots containing approximately 500 g of Quarryfield agricultural soil (Robertson-Albertyn et al, 2017;Alegria Terrazas et al, 2020) previously sieved to remove stones and large debris. Plants were grown in a randomized design in a glasshouse at 18/14°C (day/night) temperature regime with 16 h daylight that was supplemented with artificial lighting to maintain a minimum light intensity of 200 μ mol quanta m -2 s -1 .…”
Section: Growth Conditionsmentioning
confidence: 99%
“…Sequencing reads were processed using a customized bioinformatics pipeline as described before (Alegria Terrazas et al, 2020). Briefly:…”
Section: Amplicon Sequencing Reads Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting strategy is to incorporate the microbiome in breeding ( Wei and Jousset, 2017 ). There are several examples from cereal crops demonstrating the impact of breeding on the root and rhizosphere microbiome ( Alegria Terrazas et al, 2020 ; Kinnunen-Grubb et al, 2020 ). Valente et al (2020) showed that root colonization by Pseudomonas kilonensis , a plant growth promoting rhizobacterium (PGPR), was higher in ancient wheat cultivars than in modern ones under gnotobiotic conditions.…”
Section: Toward Microbiome-based Management Of Fhbmentioning
confidence: 99%